Gestational hypothyroxinemia induces ASD-like phenotypes in behavior, proinflammatory markers, and glutamatergic protein expression in mouse offspring of both sexes - González-Madrid, Enrique; Rangel-Ramírez, Ma. Andreina; Opazo, María C.; Méndez, Luis; Bohmwald, Karen; Bueno, Susan M.; González, Pablo A.; Kalergis, Alexis M.; Riedel, Claudia A. (Frontiers in Endocrinology, 2024)
Background. The prevalence of autism spectrum disorder (ASD) has significantly risen in the past three decades, prompting researchers to explore the potential contributions of environmental factors during pregnancy to ASD development. One such factor of interest is gestational hypothyroxinemia (HTX), a frequent condition in pregnancy associated with cognitive impairments in the offspring. While retrospective human studies have linked gestational HTX to autistic traits, the cellular and molecular mechanisms underlying the development of ASD-like phenotypes remain poorly understood. This study used a mouse model of gestational HTX to evaluate ASD-like phenotypes in the offspring. Methods. To induce gestational HTX, pregnant mice were treated with 2-mercapto-1-methylimidazole (MMI), a thyroid hormones synthesis inhibitor, in the tap-drinking water from embryonic days (E) 10 to E14. A separate group received MMI along with a daily subcutaneous injection of T4, while the control group received regular tap water during the entire pregnancy. Female and male offspring underwent assessments for repetitive, anxious, and social behaviors from postnatal day (P) 55 to P64. On P65, mice were euthanized for the evaluation of ASD-related inflammatory markers in blood, spleen, and specific brain regions. Additionally, the expression of glutamatergic proteins (NLGN3 and HOMER1) was analyzed in the prefrontal cortex and hippocampus. Results. The HTX-offspring exhibited anxious-like behavior, a subordinate state, and impaired social interactions. Subsequently, both female and male HTX-offspring displayed elevated proinflammatory cytokines in blood, including IL-1β, IL-6, IL-17A, and TNF-α, while only males showed reduced levels of IL-10. The spleen of HTX-offspring of both sexes showed increased Th17/Treg ratio and M1-like macrophages. In the prefrontal cortex and hippocampus of male HTX-offspring, elevated levels of IL-17A and reduced IL-10 were observed, accompanied by increased expression of hippocampal NLGN3 and HOMER1. All these observations were compared to those observed in the Control-offspring.Notably, the supplementation with T 4 during the MMI treatment prevents the development of the observed phenotypes. Correlation analysis revealed an association between maternal T4 levels and specific ASD-like outcomes. Discussion. This study validates human observations, demonstrating for the first time that gestational HTX induces ASD-like phenotypes in the offspring, highlighting the need of monitoring thyroid function during pregnancy.